Анализ качества эндодонтического лечения зубов жителей города Новосибирска по данным клинико-рентгенологического обследования (LLC "Endo Press", 2020)
The aim of research was the study of stomatological status and effectiveness of endodontic treatment in the populalion of N.city. The analysis of 492 patientg at the age of 18-74 years in x-ray dental clinic was examined. Due to the examination results, the optimal level of cemented rout canals in observed patients was revealed in 51% of cases. Statistically significant age differences of growth in endodontically treated female teeth are from 30-40 till 45-59 years, and from 60 years in men. Clinical effectiveness of endodontical treatment was 64%. The most common mistake in the rout canals failed cementing is afalse obturation meeting over 50% cases.